Remodeling reading-to-write process: a response writing task for Chinese English learners - Wu, Lingyun (Frontiers in Language Sciences, 2025)
Long recognized as a significant integrated task in major English proficiency tests, reading-to-write tasks have been researched from dimensions mainly concerning its testing validity. A further exploration into the process is essential for a better understanding of the construct and instructions of the integrated task in different cultural and educational contexts. The present study investigated the process of a response writing task by collecting data of interviews and reflective journals from 36 Chinese learners. These data were analyzed qualitatively to identify the main phases and sub-stages occurring in the reading-to-write process. The results disclosed three main phases: pre-reading, reading for writing, and writing from reading. Besides, among a set of sub-stages, planning and rereading recurred and were embedded with each other in the main phases, and therefore, bridged reading and writing. The purposes of the occurrence of the main phases and recurring sub-stages presented the dynamic agency that learners exercise. Accordingly, a new model was constructed to account for the nuanced processes as well as their connection and interaction in a reading-to-write task, providing new insight into the recursive and reciprocal nature of reading-to-write tasks for learners in the Chinese context and furthermore, into the construct of integrated academic tasks. Pedagogical suggestions for L2 learners were provided in the end.